Pengaruh Self Efficacy dan Softskill Terhadap Kesiapan Kerja Pada Siswa Kelas XI Jurusan Akuntansi SMKN 3 Bandung Tahun Ajaran 2022/2023 - Raden Dian Hardiana; A. Sobandi; Hanna Kesya Novita Rain Sagala; Muhammad Arief Ramdhany (Jurnal Pendidikan Akuntansi & Keuangan, 2023)
This research was conducted to determine the effect of Self-Efficacy and Soft skills on Job Readiness in Class XI students of the Accounting Department of SMKN 3 Bandung. This type of research uses a descriptive quantitative approach, in which information and data are obtained from respondents using a questionnaire. The population in this study were Class XI students of SMKN 3 Bandung Accounting Department consisting of 102 students. The research analysis used Multiple Linear Regression analysis. After the data is collected, the data is analyzed using SPSS software version 24. The results of this study indicate that Self-Efficacy and Soft Skills have a positive effect on work readiness. Self Efficacy and Soft Skills can explain work readiness by 0.743 or 74.3%, while 25.7% is influenced by other factors.